The pelvic floor muscle hyperalgesia (PFMH) scoring system: a new classification tool to assess women with chronic pelvic pain: multicentre pilot study of validity and reliability. (October 2015) - Bhide, Alka A.; Puccini, Federica; Bray, Rhiannon; Khullar, Vik; Digesu, G. Alessandro
Abstract: Objective: The contribution of pelvic floor muscle tenderness to chronic pelvic pain (CPP) is well established in the literature. However pelvic floor muscle hyperalgesia (PFMH) is often missed during vaginal examination of women with CPP. To our knowledge criteria for diagnosing PFMH has not been established or validated so far. The aim of this study is to assess the validity and reliability of the PFMH scoring system. Study design: Women with and without PFMH were recruited prospectively. Digital pelvic examination was performed to detect any pain. All women were asked to report of any discomfort or pain evoked by digital palpation of the PFMs and to rate the severity of pain/discomfort as none (grade 0), mild (grade I) moderate (grade II) or severe (grade III). All women were also asked to describe the severity of the pain/discomfort using a visual analogue scale (VAS). Following examination a PFMH score was given according to each patient's reactions. Intra-observer and inter-observer reliability was assessed. Construct and content validity was also determined. Results: 111 (44 symptomatic and 67 controls) were recruited. Intraobserver reliability had ICCs between 0.426 and 0.804. Interobserver reliability had ICCs between 0.724 and 0.917. There was a good correlation between PFMH scores and VAS scores (rho 0.994, p < 0.01). Total scores between symptomatic and controls were significantly different ( p < 0.01 Mann–Whitney U test). Conclusion: The PFMH scoring system is a simple, reliable, valid and easy screening tool for in the assessment of women with CPP.